Age-related decline in cognitive flexibility is associated with the levels of hippocampal neurogenesis - Amelchenko, Evgeny M.; Bezriadnov, Dmitri V.; Chekhov, Olga A.; Anokhin, Konstantin V.; Lazutkin, Alexander A.; Enikolopov, Grigori (Frontiers in Neuroscience, 2023)
Aging is associated with impairments in learning, memory, and cognitive flexibility, as well as a gradual decline in hippocampal neurogenesis. We investigated the performance of 6-and 14-month-old mice (considered mature adult and late middle age, respectively) in learning and memory tasks based on the Morris water maze (MWM) and determined their levels of preceding and current neurogenesis. While both age groups successfully performed in the spatial version of MWM (sMWM), the older mice were less efficient compared to the younger mice when presented with modified versions of the MWM that required a reassessment of the previously acquired experience. This was detected in the reversal version of MWM (rMWM) and was particularly evident in the context discrimination MWM (cdMWM), a novel task that required integrating various distal cues, local cues, and altered contexts and adjusting previously used search strategies. Older mice were impaired in several metrics that characterize rMWM and cdMWM, however, they showed improvement and narrowed the performance gap with the younger mice after additional training. Furthermore, we analyzed the adult-born mature and immature neurons in the hippocampal dentate gyrus and found a significant correlation between neurogenesis levels in individual mice and their performance in the tasks demanding cognitive flexibility. These results provide a detailed description of the age-related changes in learning and memory and underscore the importance of hippocampal neurogenesis in supporting cognitive flexibility.